2007
DOI: 10.1055/s-2007-989277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment for Spinal Cord Tethering in Patients with Anorectal Malformations

Abstract: Based on the results of this study, we recommend routine MRI examination of patients with ARM and early untethering surgery in cases with SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
2
11
1
5
Order By: Relevance
“…The benefit of detethering surgery is also controversial. The results of many studies suggest that neurosurgical release of tethered spinal cord has a beneficial effect on urinary [9,12,38,39], orthopedic [9], and bowel function [39]. Evidence of such a beneficial effect was not clearly observed in bowel function in the present study.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The benefit of detethering surgery is also controversial. The results of many studies suggest that neurosurgical release of tethered spinal cord has a beneficial effect on urinary [9,12,38,39], orthopedic [9], and bowel function [39]. Evidence of such a beneficial effect was not clearly observed in bowel function in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Another important aspect of spinal cord tethering is that it is not a static condition, with several reports of progressive neurologic deficit in children with tethered cord syndrome [38,41]. The present study includes one patient who showed newly developed tethered cord syndrome based on the results of serial MRI, which is similar to the previous report [9]. These patients have an anatomically stable but growing lipomatous mass because of increased lipogenesis within the spinal canal during the early years of life.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…6,[13][14][15][16][17][18] This can best be explained by the diagnostic methods used. In the studies that detected a higher prevalence, up to 35 to 46%, 6,18 patients were screened for TSC using MRI. In contrast, we primarily screened with ultrasonography and only performed an MRI on indication, either based on ultrasonography findings or based on clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…According to western literature craniospinal abnormalities especially spinal abnormalities are very common among patients with anorectal malformation; incidence is up to 46% [3][4][5][6][7]. In India it is up to 10% [8]. Some studies suggest that high resolution ultrasonography can detect craniospinal abnormalities efficiently but recently most of the studies suggest MRI as a routine investigation in patients with anorectal malformation because of high incidence of spinal abnormalities association with ARM [9].…”
Section: Discussionmentioning
confidence: 99%